Glutathione protects human nucleus pulposus cells from cell apoptosis and inhibition of matrix synthesis. (April 2014) - Yang, Dazhi; Wang, Daidong; Shimer, Adam; Shen, Francis H.; Li, Xudong; Yang, Xinlin
Abstract Cell death (apoptosis and necrosis) and extracellular matrix destruction induced by oxidative stress have been suggested to be closely involved in the process of disc degeneration. Glutathione, a natural peptide as a powerful antioxidant in human cytoplasm, plays an important role in protecting living cells. This study is to investigate whether glutathione could retard degenerated phenotypes in cultured disc cells. Human nucleus pulposus cells were isolated and cultured in alginate beads and subsequently treated with a pro-oxidant H2O2 alone or a pro-inflammatory cytokine IL-1β alone or either of them together with glutathione. It was shown that H2O2 dose-dependently promoted nucleus pulposus cell apoptosis detected by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining and decreased mRNA levels of matrix proteins aggrecan and type II collagen determined by quantitative reverse transcription-polymerase chain reaction (RT-PCR). IL-1β could induce production of nitric oxide and decrease of proteoglycan, detected by the Griess reagent and the dimethyl methylene blue, respectively. The deleterious effects of either H2O2 or IL-1β could be efficiently prevented by glutathione. These results indicated that glutathione might be considered as an option for intervention of disc degeneration.